Research activity and capability in the European reference network MetabERN - Heard, Jean-Michel; Bellettato, Cinzia; Kölker, Stefan (Orphanet journal of rare diseases, 2019)
MetabERN is one of the 24 European Reference Networks created according to the European Union directive 2011/24/EU on patient’s rights in cross border healthcare. MetabERN associates 69 centres in 18 countries, which provide care for patients with Hereditary Metabolic Diseases, and have the mission to reinforce research and provide training for health professionals in this field. MetabERN performed a survey in December 2017 with the aim to produce an overview documenting research activities and potentials within the network. As the centres are multidisciplinary, separated questionnaires were sent to the clinical, university and laboratory teams. Answers were received from 52 out of the 69 centres of the network, covering 16 countries. A descriptive analysis of the information collected is presented.
Gesehen am 02.07.2019